Estimating time‐varying RSA to examine psychophysiological linkage of marital dyads. (8th April 2015) - Gates, Kathleen M.; Gatzke‐Kopp, Lisa M.; Sandsten, Maria; Blandon, Alysia Y.
Abstract One of the primary tenets of polyvagal theory dictates that parasympathetic influence on heart rate, often estimated by respiratory sinus arrhythmia (RSA), shifts rapidly in response to changing environmental demands. The current standard analytic approach of aggregating RSA estimates across time to arrive at one value fails to capture this dynamic property within individuals. By utilizing recent methodological developments that enable precise RSA estimates at smaller time intervals, we demonstrate the utility of computing time‐varying RSA for assessing psychophysiological linkage (or synchrony) in husband‐wife dyads using time‐locked data collected in a naturalistic setting.